Do foco de prevenção ao ódio à marca: mediações cognitivo-emocionais - Rosa, Jean Carlos de Oliveira (Universidade do Vale do Rio dos Sinos, 2025)
This thesis investigates the role of regulatory focus in the formation of negative emotional responses toward brands, with an emphasis on the phenomenon of brand hate. Drawing on Regulatory Focus Theory, it is argued that consumers with a prevention orientation tend to react more intensely to negative brand-related stimuli, expressing hostile emotions and avoidance behaviors. Three experimental studies were conducted, combining self-reported measures with neurophysiological indicators obtained through EyeTracking and FaceReader. This multimethod approach enabled a more accurate capture of the cognitive and emotional processes underlying consumers’ negative reactions to brands, enhancing the understanding of nonverbal responses in consumption contexts. The results indicate that a prevention focus is associated with a higher propensity for brand hate, mediated by negative emotional reactions and unfavorable cognitive evaluations. The thesis contributes to the advancement of the literature on consumer emotions and brand management in crisis contexts, offering theoretical and practical insights for communication strategies and reputation damage mitigation.
Keywords: Foco de prevenção; Ódio à marca; Processamento cognitivo; Respostas emocionais negativas; Boca a boca negativo; Prevention focus; Brand hate; Negative emotional responses; Cognitive processing; Negative word-of-mouth; ACCNPQ::Ciências Sociais Aplicadas::Administração